The Tumor Immunoenvironment 2013
DOI: 10.1007/978-94-007-6217-6_15
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment may Shape the Function and Phenotype of NK Cells Through the Induction of Split Anergy and Generation of Regulatory NK Cells

Abstract: Cytotoxic function of NK cells is suppressed in the tumor microenvironment by a number of distinct effectors. Furthermore, decreased peripheral blood NK cell cytotoxicity has been documented in cancer patients. We have previously demonstrated evidence for the role of NK cells in specific elimination of stem cells and not their differentiated counterparts. In this regard, NK cells were found to mediate significant cytotoxicity against primary oral squamous carcinoma stem cells (OSCSCs) as compared to their more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Based on these results, we have proposed, that NK cells play a significant role in differentiation of cells by providing critical signals via secreted cytokines as well as direct cell-cell contact 18. In addition, we have demonstrated that human monocytes promote significant split anergy in NK cells 16, 19, 21, 66-68. Induction of split anergy in NK cell effector function is thought to ultimately aid in driving differentiation of healthy, as well as transformed stem-like cells 19, 66-69.…”
Section: Discussionmentioning
confidence: 81%
“…Based on these results, we have proposed, that NK cells play a significant role in differentiation of cells by providing critical signals via secreted cytokines as well as direct cell-cell contact 18. In addition, we have demonstrated that human monocytes promote significant split anergy in NK cells 16, 19, 21, 66-68. Induction of split anergy in NK cell effector function is thought to ultimately aid in driving differentiation of healthy, as well as transformed stem-like cells 19, 66-69.…”
Section: Discussionmentioning
confidence: 81%
“…The stage of differentiation of many tumors including GBM is predictive of their sensitivity to NK cell lysis since CSCs/poorly differentiated GBM tumors are targets of NK cells, whereas those differentiated with split anergized NK cell supernatants display resistance to NK cell-mediated cytotoxicity [32, 4146]. We have shown that NK cells play a significant role in differentiation of tumors by providing critical signals via secreted IFN-γ and TNF-α, as well as direct cell–cell contact [10, 35].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that NK cells play a significant role in differentiation of tumors by providing critical signals via secreted IFN-γ and TNF-α, as well as direct cell–cell contact [10, 35]. Furthermore, tumor differentiation is likely supported by signals from other immune effectors, such as monocytes and macrophages within the tumor stroma to induce split anergy in NK cells [41, 4346]. Interestingly, significantly higher amounts of NK supernatant containing IFN-γ were required to differentiate X02GB in comparison with OSCSCs resulting in tumor growth inhibition, upregulation of CD54, B7H1 and MHC-I expression and resistance to NK cell-mediated cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the deletion of NF-κB in tumors was found to increase NK cell-mediated cytotoxicity and secretion of IFN-γ significantly ( 2 , 3 ), and induce auto-immunity and inflammation in vivo ( 63 , 64 ). Moreover, conditional knockout of STAT3 in hematopoietic cells was found to result in the induction of colitis in mice due to chronic gut inflammation ( 57 , 65 ). Furthermore, we have shown previously that NK cells target poorly differentiated cells or stem cells with lower expression of many important differentiation receptors ( 45 , 60 , 66 ).…”
Section: Discussionmentioning
confidence: 99%